The Cape Barren Goose in Victoria, Australia: management related to agriculture - Dorward, D F; Norman, F I; Cowling, S J (Wildfowl, 1980)
Cape Barren Geese Cereopsis novaehollandiae from breeding grounds on islands off Wilson’s Promontory, Victoria, visit mainland pastures some 40 km distant during summer in a flock of up to 300 birds. Attempts to attract geese to certain areas and to minimize the agricultural problems are described. Their impact on agricultural interests is assessed in terms of amount of pasture consumption, fouling of water places, and possible transmission of disease. These problems are compared with those for Cape Barren Geese elsewhere in Australia and for true geese in Britain. The suggested long-term solution is acquisition of appropriate land and its specific management for geese.